2003
DOI: 10.1002/anie.200390266
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytic Carbon–Phosphorus Ylide Reaction: Phosphane‐Catalyzed Annulation of Allylic Compounds with Electron‐Deficient Alkenes

Abstract: To ensure high efficiency, turning a stoichiometric reaction into a catalytic one, and developing new catalytic reactions have been long-standing goals in modern synthesis. Ylide reactions are among the most powerful tools for constructing olefins [1] and small rings, [2] but few are catalytic, in particular those involving phosphorus ylides.[3] The first example of a catalytic Wittig-type reaction of arsenic ylides, in which a stoichiometric amount of reducing agent was used to regenerate the arsane, was desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(82 citation statements)
references
References 39 publications
0
79
0
3
Order By: Relevance
“…[3] In the presence of 10 mol-% PPh 3 and 1.5 equiv. of K 2 CO 3 additive, in toluene as solvent at 90°C, [3 + 2] annulation of modified MBH adducts 1, including bromides and acetates, with electron-deficient alkenes such as maleimides 3 or α, -unsaturated ketones 4 readily occurred, affording multifunctionalized cyclopentenes 5 or 6 in moderate to good yields with high diastereoselectivity (Scheme 2).…”
Section: Intermolecular [3 + 2] Annulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In the presence of 10 mol-% PPh 3 and 1.5 equiv. of K 2 CO 3 additive, in toluene as solvent at 90°C, [3 + 2] annulation of modified MBH adducts 1, including bromides and acetates, with electron-deficient alkenes such as maleimides 3 or α, -unsaturated ketones 4 readily occurred, affording multifunctionalized cyclopentenes 5 or 6 in moderate to good yields with high diastereoselectivity (Scheme 2).…”
Section: Intermolecular [3 + 2] Annulationsmentioning
confidence: 99%
“…[51] Through the joint forces of computation and isotopic labeling experiments, the authors demonstrated that the reaction required the cocatalysis of triphenylphosphane and water. Mechanistically, the catalytic cycle starts with the formation of a zwitterionic intermediate 114, generated from α-methyl allenoate 113 and PPh 3 . Then a water-assisted [1,4] As demonstrated by Kwon [41] and Ye, [52] α-alkyl allenoates could serve as a versatile set of C 4 synthons in phosphanecatalyzed [4 + 2] annulations with imines, ketones, and electron-deficient alkenes, affording efficient syntheses of tetrahydropyridines, dihydropyrans, and cyclohexenes.…”
Section: Annulations Involving α-Substituted Allenesmentioning
confidence: 99%
“…[64] Presumably, the phosphine triggers the reaction through salt formation with the allylic bromide. The inorganic base then generates the allylic anion setting up for the cycloaddition reaction.…”
Section: Cycloaddition Reactions Of Activated Alkynes and Allenesmentioning
confidence: 99%
“…60 These new phosphonium species grant access to new reaction pathways with nucleophiles, electrophiles, and electrophile–nucleophiles.…”
Section: Phosphine Catalysis Of Morita–baylis–hillman Alcohol Derimentioning
confidence: 99%
“…60 By installing a β'-acetate or β'- tert -butylcarbonate group, novel phosphonium species are obtained through new annulation pathways. The mechanism proceeds with conjugate addition into the MBHAD 109 with the ejection of the β'-leaving group, forming the phosphonium species 110 (Scheme 70).…”
Section: Phosphine Catalysis Of Morita–baylis–hillman Alcohol Derimentioning
confidence: 99%